A trial of alemtuzumab adjunctive therapy in allogeneic hematopoietic cell transplantation with minimal conditioning for severe combined immunodeficiency. (30th June 2014) - Dvorak, Christopher C.; Horn, Biljana N.; Puck, Jennifer M.; Adams, Stuart; Veys, Paul; Czechowicz, Agnieszka; Cowan, Morton J.
Abstract For infants with SCID the ideal conditioning regimen before allogeneic HCT would omit cytotoxic chemotherapy to minimize short‐ and long‐term complications. We performed a prospective pilot trial with alemtuzumab monotherapy to overcome NK‐cell mediated immunologic barriers to engraftment. We enrolled four patients who received CD34‐selected haploidentical cells, two of whom failed to engraft donor T cells. The two patients who engrafted had delayed T‐cell reconstitution, despite rapid clearance of circulating alemtuzumab. Although well‐tolerated, alemtuzumab failed to overcome immunologic barriers to donor engraftment. Furthermore, alemtuzumab may slow T‐cell development in patients with SCID in the setting of a T‐cell depleted graft.